what will be the answer
Attachments:
![](https://hi-static.z-dn.net/files/d26/b4b2ed36e3c746c73b60a16238b7cdc0.jpg)
Answers
Answered by
0
Answer:
1) 0 remainder
Step-by-step explanation:
Answer is right so Thanks,
But not right so sorry.
Answered by
20
Solution :-
Given,
p (x) =
g (x) = x - 2
Let g (x) = 0 => x - 2 = 0 => x = 2
By the Remainder Theorem, When p (x) is Divided by (x - 2), then the Remainder is p (2)
Now, p (2) =
Hence, The Required Remainder is 7...
Option B is the Right Answer...
--
#HappyLearning!
Please Give a Thanks and Mark this Answer as the Brainliest...
Similar questions
Political Science,
4 months ago
Math,
4 months ago
Math,
4 months ago
Computer Science,
8 months ago
English,
1 year ago
History,
1 year ago